Geospatial Assessment of Floods in Western Nepal - Sugam Subedi; Gandhiv Kafle; Shankar Tripathi (The Scientific World Journal)
Floods are major problems, and their coexistence poses a potent threat, which cannot be eradicated but has to be managed. Extreme affects untold numbers of people, taxing economies, disrupting food production, creating unrest, and prompting migrations. There is much more that can be done to understand the effects of floods, particularly to help protect the poorest and most vulnerable. This research was carried out in the affected area of Bhimdatta municipality and aimed to find out the flood event of 2013 and present the scenario done for flood disaster management. The primary data were collected by direct observation and key informant survey. Landsat images were downloaded from USGS websites, and secondary information was collected through previous research and articles. The data were analyzed by using ArcGIS. It was found that the flood had created a negligible impact on the forest, high impact on the river itself, and average impact on land. 0.13% of forests, 17.38% of land, and 82.48% of river bodies were affected by the flood of 2013. Different governmental and nongovernmental organizations played an effective role for flood disaster management.